Potassium Therapy in Patients with Hypokalemic Periodic Paralysis in RSUD Kabupaten Empat Lawang: A Case Report - Aprilia, Sintia Eka; Tambun, Oktavianus (The Indonesian Journal of General Medicine, 2024)
Introduction: Hypokalemic periodic paralysis (HypoPP) is a rare skeletal muscle channelopathy characterized by episodic attacks of moderate to severe flaccid muscle tetraparesis accompanied by hypokalemia. This case report aims to discuss the case and management of hypokalemic periodic paralysis with potassium therapy at RSUD Kabupaten Empat Lawang. Case Presentation: A 29-year-old female presented with sudden bilateral limb weakness, vomiting, and nausea. She had no breathing, swallowing issues, or pain. Physical examination showed reduced muscle strength and epigastric tenderness. Laboratory tests indicated elevated leukocytes and decreased kalium. Diagnosed with hypokalemic periodic paralysis and a UTI, she received IV fluids, potassium chloride, and other supportive treatments, leading to immediate condition resolution. Conclusion: Hypokalemic Periodic Paralysis (HypoPP) is a rare neuromuscular disorder characterized by periodic muscle weakness ranging from mild to complete paralysis.. The etiology in this case was secondary to hyperemesis. Failure to diagnose and manage periodic paralysis can be fatalIt can lead to respiratory failure and death. Treatment involves potassium supplementation and monitoring for cardiac complications.